PUBLIC ADMINISTRATION AND SCIENCE - Rakhimova Dilfuza Nigmatovna (Modern American Journals, 2025)
The article considers Current issues of public administration system and priority areas of development. The experience of developed countries in the development of public administration system has been studied. The article analyses the strengths and weaknesses of the public administration system. Proposals for new projects to improve public administration have been developed.
Keywords: Public administration, system, priority areas, transparency and openness, e-government, economic growth and prosperity, public authorities, rule of law, reduce the possibility of corruption, new technologies.